Biogeochemical niches and trophic plasticity of shallow and mesophotic corals recovering from mass bleaching. Issue 7 (1st June 2022) - Radice, Veronica Z.; Fry, Brian; Brown, Kristen T.; Dove, Sophie; Hoegh‐Guldberg, Ove
Abstract: The differential survival of corals and their recovery from oceanic thermal stress is related not only to coral bleaching susceptibility but also physiological plasticity including trophic strategy. We investigated post‐bleaching event recovery of three morphologically diverse, reef‐building coral species from shallow (10 m) and mesophotic (30 m) reefs across the Maldives archipelago. Trophic plasticity was evaluated by carbon and nitrogen contents and stable isotopes of coral hosts and their algal symbionts including isotopic niche position and size. Seawater temperatures recorded before, during, and after the mass coral bleaching event revealed significant thermal stress in both shallow and mesophotic reefs although cumulative warming appeared lower in mesophotic reefs (9.0 vs. 5.9 degree heating weeks, respectively). Ten months following thermal stress, increased nitrogen stable isotope (δ 15 N) values in all three coral host species without concurrent changes in water column δ 15 N indicated enhanced heterotrophic feeding during thermal stress and/or recovery. Host C:N decreased in all species post‐bleaching event while host carbon content (%C) decreased in shallow, more autotrophic populations of two species, suggesting prolonged stress. Host carbon stable isotope (δ 13 C) values were lower in mesophotic, more heterotrophic populations of two species compared to shallow counterparts. Biogeochemical and isotopic niches both showed different niche specialization among the three species. Consistent shifts in host isotopic niche positions support a conserved host response mechanism (heterotrophy) to oceanic thermal stress, but shallow and mesophotic corals still had not fully recovered almost one year after the bleaching event.